TRANSLATION PROCEDURE IN THE TRANSLATION OF MY LITTLE PONY SOUNDTRACK MOVIE INTO ITS INDONESIAN VERSION - Hapsari, Nunuk Tri (Conscientia - Journal on Language, Literature, and Culture, 2024)
Translating children's songs from English to Indonesian involves more aspects of the translation process. It requires cultural adjustment and adaptation to suit the local context and target audience. Qualitative study and comparative method were used to reveal the word choices and translation procedures used in translating the soundtrack of the animated children's movie, My Little Pony into Indonesian. This study aims to find the appropriate translation procedures used to maintain the meaning and message contained in the songs of My Little Pony movie as SL into its translation in Indonesian song version. This study found that there was a distortion of meaning in the translation of the SL song lyrics into the TL. Meanwhile, the cultural adaptation in diction and context was used to maintain the meaning and message contained in the song and can be well understood by children as the main target audience of the animated film. The equivalent meaning is obtained by maintaining and paying attention to the context of the SL song sentences/lyrics in the TL song lyrics. By maintaining the context, the meaning of the SL song lyrics is well conveyed in the TL song lyrics.